Metallomicelle catalyzed aerobic tandem desilylation/Glaser reaction in water. Issue 11 (4th April 2019) - Tang, Shanyu; Li, Longjia; Ren, Xuanhe; Li, Jiao; Yang, Guanyu; Li, Heng; Yuan, Bingxin
Abstract : The copper complexes of PEG-grafted nitrogen ligands serve as metallomicellar nanoreactors for the aerobic tandem desilylation/Glaser coupling of TMS-protected alkynes in water. Abstract : PEG-grafted nitrogen ligands were synthesized. The corresponding copper complexes serve as metallomicellar nanoreactors for the aerobic tandem desilylation/Glaser coupling of TMS-protected alkynes in water. The protocol is also suitable for base-free homocoupling of terminal alkynes. The metallomicellar catalyst could be recycled 5 times with minor loss of reactivity.